Case Report: Molecular and immunological insights into primary extramedullary plasmacytoma: discovery of a novel IGH::NFKB1 fusion and its impact on disease progression and treatment - Gao, Ziting; Li, Dongbing; Zhang, Tingting; Su, Wenfeng; Xu, Jintao; Zhuang, Yuanjie; Cao, Rong; Xie, Yufei; Lang, Xingping; Chen, Huafei; Fan, Chunlin; Yang, Xi; et al. (Frontiers in Immunology, 2025)
Extramedullary Plasmacytoma (EMP) is a rare plasma cell neoplasm that originates outside the bone marrow. Primary Extramedullary Plasmacytoma with Diffuse Lymph Node Involvement (PLNEMP) is exceptionally rare. Here, we report a unique case of PLNEMP and significant bone destruction, characterized by a novel IGH::NFKB1 fusion gene. A 60-year-old Chinese male presented with palpable enlarged lymph nodes in the left inguinal region. After completing laboratory tests and examinations, it was suggested that there was monoclonal immunoglobulinemia and multiple bone destruction. Pathological examination of the left inguinal lymph node biopsy showed plasmacytoma with monoclonal gammopathy. Genomic profiling identified a novel IGH::NFKB1 fusion gene. The two 3′ regulatory region (3′RR) enhancers of the IGH locus were fused to a region 379 bp upstream of NFKB1 exon 1, resulting in overexpression of NFKB1. The patient received four cycles of chemotherapy with Mitoxantrone hydrochloride liposome (Lipo-MIT) combined with Bortezomib, Pomalidomide, and Dexamethasone (MVPD), achieving very good partial remission (VGPR) in hematological and partial remission (PR) in extramedullary disease. Subsequently, he underwent autologous stem cell transplantation (ASCT) followed by BCMA CAR-T cell therapy. At 8 months post-transplantation, complete remission (CR) was achieved in hematological parameters, and the extramedullary disease showed a response greater than PR. The patient has survived for 26 months so far. This case highlights the importance of recognizing the rare presentation of PEMP with diffuse lymph node involvement and significant bone destruction. The presence of the novel IGH::NFKB1 fusion gene provides insights into the potential role of the NF-κB pathway in the pathogenesis of this disease. The successful treatment with MVPD chemotherapy, ASCT, and BCMA CAR-T therapy demonstrates the potential efficacy of this combined therapeutic approach in achieving long-term remission and survival in such rare cases. Further studies are warranted to explore the therapeutic implications of targeting the NF-κB pathway in similar cases of EMP with bone destruction.